Mechanical alignment tolerance of a cruciate-retaining knee prosthesis under gait loading—A finite element analysis - Luan, Yichao; Wang, Huizhi; Fang, Chaohua; Zhang, Min; Li, Junwei; Zhang, Ningze; Liu, Bolun; Su, Jian; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2023)
Component alignment is one of the most crucial factors affecting the clinical outcome and survival of total knee arthroplasty. This study aimed to investigate how coronal, sagittal, and transverse malalignment affects the mechanical behavior of the tibial insert, and to determine a suitable alignment tolerance on the coronal, sagittal, and transverse planes. A finite element model of a cruciate-retaining knee prosthesis was assembled with different joint alignments (-10°, -7°, -5°, -3°, 0°, 3°, 5°, 7°, 10°) to assess the effect of malalignment under gait loading. The results showed that varus or valgus, extension, internal rotation, and excessive external rotation malalignments increased the maximum Von Mises stress and contact pressure on the tibial insert. The mechanical alignment tolerance of the studied prosthesis on the coronal, sagittal, and transverse planes was 3° varus to 3° valgus, 0° to 10° flexion, and 0° to 5° external rotation, respectively. This study suggests that each prosthesis should include a tolerance range for the joint alignment angle on the three planes which may be used during surgical planning.